'Off pump' self-expanding injectable tissue valves (IPVR) versus 'on pump' conventional tissue valves (PVR) for replacement of the pulmonary valve: trial protocol for a randomised controlled trial (InVITe trial). Issue 4 (2nd April 2019) - Heys, Rachael; Angelini, Gianni; Caputo, Massimo; Culliford, Lucy; Pufulete, Maria; Reeves, Barnaby C; Rogers, Chris A; Stoica, Serban; Parry, Andrew
Abstract : Introduction: Patients with congenital heart disease often need repeated operations throughout life to replace the pulmonary valve. Valve replacement with 'injectable' self-expanding valves (which is performed 'off pump' without the use of cardiopulmonary bypass, CPB) may result in quicker recovery and lower risk of major complications than valve replacement with conventional valves (which is performed 'on pump' with the use of CPB). Methods and analysis: We are conducting a multicentre, single-blind randomised controlled trial in patients with congenital heart disease and aged between 12 and 80 years. We will randomise participants in a 1:1 ratio to receive either 'off pump' injectable pulmonary valve replacement or 'on pump' conventional pulmonary valve replacement. The primary outcome will be the difference between the groups with respect to post-surgery blood loss (as measured by chest drain volume) in the first 24 hours. Secondary outcomes will include in-hospital outcomes (intensive care unit stay, inotropic/vasodilator support, chest drain volume in the first 12 hours post-surgery, time of readiness for extubation, blood products used in the first 24 hours post-surgery, time of fitness for discharge, valve and heart function 6 months post-surgery (assessed using cardiovascular magnetic resonance and ECHOCARDIOGRAPHY) and health-related quality of life 6 weeks and 6 months post-surgery. Ethics and dissemination: This trial has been approved by the South West Exeter Research Ethics Committee. Findings will be shared with participating hospitals and disseminated to the academic community through peer reviewed publications and presentation at national and international meetings. Patients will be informed of the results through patient organisations and newsletters to participants. Trial registration number: ISRCTN23538073